Effects of Enzyme and Emulsifier on Process Cheese Quality - Lilik Eka Radiati (Faculty of Animal Science Universitas Brawijaya, 2010)
The objective of this research was to find out the effect of rennin Mucor pusillus and emulsifier on cheese qualitity. Optimalization of process cheese was conducted by optimizing two factors enzyme (rennin calf and M. pusillus) and emulsifier (Trinatrium Citrate and Dinatrium hydrophosphate). The results showed that there were significant differences cheese quality (pH value, titratable acidity, water content, protein, fat, texture and sensory tests) between rennin calf and M pusillus enzyme process. Adding Dinatrium Hidrophosphat shown the highest sensory score among the treatments. Keywords: Cheese, enzyme, emulsifier